The Rural Development and Employment in Albania - Meçe, Manuela; Ribaj, Artur (European Journal of Economics and Business Studies, 2019)
Public institutions in Albania play an important role in the functioning, regulation and development of the rural areas, including their support to the rural labor market as an important mechanism for the allocation of labor, resources and income generation. The governments’ efforts emphasize the prioritization of rural employment as crucial for development of Albania. But, this paper conclusions that many young Albanians from rural countryside would like to run away from their country, not because they don’t love their country, but because they see no employment (and livelihood) perspective. The economic development of the country seems more as a residual rather than prosperous, despite many foreign experts and donors trying over 25 past years to present a sustainable economic development model. Informal work arrangements remain widespread across many economic activities and the division between unemployment and informal work (employment) is still blurred. Albanians from rural countryside should be drawn more to farming than in the recent past. Government institutions should reflect a clear rise in the status of farming compared to the recent past, improving the respective legal framework, addressing constraints on access to farming activities and borrowing (or financing) and adapting fiscal policies which will motivate and incentive them to be drawn more to farming than in the recent past.
Keywords: The Rural Development and Employment in Albania